The Effect of Store Display and Store Atmosphere towards Purchasing Decision at Gramedia Pandanaran Semarang - Yumei Ajeng Putri; Rodhiyah Rodhiyah; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2015)
Marketing product in business world have important role which connected to purchase decision. Purchasing decision can be triggered by store display which catch customers first impression. Therefore, create store atmosphere is needed for giving comfort to customers when they are in the store. All these aspects must be mutually support to achieve the purpose of Gramedia Pandanaran.The purpose of this study was to determine the effect of store display and store atmosphere on purchase decision at Gramedia Pandanaran Semarang. This research method is explanatory, with the technique of collecting data through interviews with questionnaires, observation, and study of literature. Accidental sampling and purposive sampling technique was used with a sample of 100 people. The analysis technique used is quantitative and qualitative by validity test, reliability test, simple and multiple regression, correlation coefficient, coefficient of determination (R2), cross-tabulation, and significant test (t test and F test).Results and discussion showed that store display classified as good, but there are still classified as good enough. Store atmosphere classified as good, but there are still classified as bad. Purchasing decision classified as good, but there are still classified as bad. Store display have significant effect towards purchasing decision (16.4 percent). The better store display then the better purchasing decision. Store atmosphere have significant effect towards purchasing decision (16.4 percent). The better store atmosphere then the better purchasing decision.The research conclusion of store display and store atmosphere relatively good, even though have some weak points. Recommendation for management are maintain the neatness of display anytime. Arrange a good scent in the store. Increase innovation and variation product so that customer will make repeat purchases. Then, need for further research by the company or an outside party on the other independent variables such as the effect of live events, price, promotion, advertisement, store image, and store services.